2010
DOI: 10.1016/j.cell.2010.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Specific c-Fos Expression Emerges from the Spatiotemporal Control of ErbB Network Dynamics

Abstract: Summary Activation of ErbB receptors by epidermal growth factor (EGF) or heregulin (HRG) determines distinct cell fate decisions, although signals propagate through shared pathways. Using modeling and experiments, we unravel how EGF and HRG generate distinct, all-or-none responses of the phosphorylated transcription factor c-Fos. In the cytosol, EGF induces transient and HRG induces sustained ERK activation. In the nucleus, however, ERK activity and c-fos mRNA expression are transient for both ligands. Knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
293
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(308 citation statements)
references
References 55 publications
(45 reference statements)
11
293
2
Order By: Relevance
“…Indeed, by sequestering Cdc42, Mig-6 inhibits hepatocyte growth factor (HGF)-induced cell migration (Gotoh 2009 (Camps et al 1998). The class I DUSPs (1/2/4/5) are inducible nuclear phosphatases, whose expression can be detected within an hour after activation of the ErbB receptors (Owens and Keyse 2007;Nakakuki et al 2010). A recent study found transient ERK activity in the nucleus, whereas ERK activity in the cytoplasm was sustained.…”
Section: Feedback Loops Via Transcriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, by sequestering Cdc42, Mig-6 inhibits hepatocyte growth factor (HGF)-induced cell migration (Gotoh 2009 (Camps et al 1998). The class I DUSPs (1/2/4/5) are inducible nuclear phosphatases, whose expression can be detected within an hour after activation of the ErbB receptors (Owens and Keyse 2007;Nakakuki et al 2010). A recent study found transient ERK activity in the nucleus, whereas ERK activity in the cytoplasm was sustained.…”
Section: Feedback Loops Via Transcriptionmentioning
confidence: 99%
“…A recent study found transient ERK activity in the nucleus, whereas ERK activity in the cytoplasm was sustained. These different ERK kinetics in the cytoplasm and the nucleus were explained by inducible expression of several nuclear DUSPs since simultaneous knockdown of these phosphatases substantially prolonged ERK activation in the nucleus (Nakakuki et al 2010).…”
Section: Feedback Loops Via Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulation of gene expression on the level of mRNA and total protein is quite common (Kolch et al, 2015;Nakakuki et al, 2010). Examples that are particularly relevant for cancer are regulation of the cell-cycle or the DNA-damage response.…”
Section: Introductionmentioning
confidence: 99%